People power in São Tomé and Principe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Increasing poverty in the country has led to a mushrooming of small community associations set up by women over the past decade especially in rural areas. Some associations support small farmers for improving production techniques and marketing....